2012
DOI: 10.3892/ijo.2012.1719
|View full text |Cite
|
Sign up to set email alerts
|

Genistein, a soy phytoestrogen, prevents the growth of BG-1 ovarian cancer cells induced by 17β-estradiol or bisphenol A via the inhibition of cell cycle progression

Abstract: An endocrine disrupting chemical (EDC) is a global health concern. In this study, we examined the effects of genistein (GEN) on bisphenol A (BPA) or 17β-estradiol (E2)-induced cell growth and gene alterations of BG-1 ovarian cancer cells expressing estrogen receptors (ERs). In an in vitro cell viability assay, E2 or BPA significantly increased the growth of BG-1 cells. This increased proliferative activity was reversed by treatment with ICI 182,780, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
0
37
1
Order By: Relevance
“…8,9 Genistein (GEN) is a major bioactive isoflavone obtained primarily from soybeans. 10 It has been demonstrated that GEN has numerous activities, such as inhibition of protein tyrosine kinase, antioxidation, antiapoptosis, and deregulation of mitochondrial membrane pore permeability.…”
Section: Introduction Amentioning
confidence: 99%
“…8,9 Genistein (GEN) is a major bioactive isoflavone obtained primarily from soybeans. 10 It has been demonstrated that GEN has numerous activities, such as inhibition of protein tyrosine kinase, antioxidation, antiapoptosis, and deregulation of mitochondrial membrane pore permeability.…”
Section: Introduction Amentioning
confidence: 99%
“…In our study, genistein and scutellarin EFFECT OF FLAVONOIDS ON SIGNALING PROTEINS 247 downregulate the expression of cyclin D1, which is a cell cycle regulatory protein and the regulation of cyclin D1 is responsible for the G1/S cell cycle transition (35,36). In a different study, baicalein exhibited induced cell cycle arrest in osteosarcoma cells by suppressing the expression levels of cyclin D1 and Cdk4 (35)(36)(37). Another plant-derived flavonoid, quercetin, was also shown to dysregulate the expression of cyclin D1 in cervical cancer, HeLa cells (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 84%
“…Genistein induces a G2/M cell cycle arrest in PC3 and LNCaP, prostate cancer cells; H460 and H322, nonsmall cell lung cancer cells as well as MDA-MB-231 and MCF-10CA1a, breast cancer cells (40). Moreover, Scutellaria baicalensis can greatly inhibit hepatocellular carcinoma cell growth via the G 2 /M phase arrest (15,(35)(36)(37)(38)41). Genistein induced an upregulation of p21WAF1, downregulation of cyclin B, and induction of apoptosis in prostate cancer cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ERs, meanwhile, may mediate cytoplasmic signaling cascades via nongenomic pathways by interacting with receptor tyrosine kinases in a cell membrane. Epidermal growth factor receptor (EGFR) and insulin-like growth factor-1 receptor (IGF-1R) are typical receptor tyrosine kinases that provoke a mitogenic cytoplasmic signaling by activating extracellular signaling-regulated kinase (ERK) cascade (Improta-Brears et al, 1999) and phosphatidylinositol 3-kinase (PI3-kinase) route (Castoria et al, 2001;Sun et al, 2001) and they are also closely linked to ER signaling, thus providing an intricate pathogenesis in estrogen-dependent cancers (Massarweh and Schiff, 2006). Toxicology and Applied Pharmacology 272 (2013) [637][638][639][640][641][642][643][644][645][646] In the present study, we focused on the specific crosstalk between ER and IGF-1R signaling pathways in estrogen-responsive BG-1 ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%